Cholesterol partially rescues the inhibition effect of pravastatin on keratinocytes proliferation by regulating cell cycle relative proteins through AKT and ERK pathway. Issue 6 (28th September 2020) - Li, Mingcong; Jin, Rui; Qi, Yinliang; Zhou, Hong; Zhu, Tingting; Liu, Li; Gu, Yanan; Luan, Kang; Luo, Xin; Zhang, Shengquan
Abstract: Mevalonate pathway plays a key role in skin physiological process in human. Recently, it has been reported that mutation of some genes in the mevalonate pathway cause disseminated superficial actinic porokeratosis (DSAP). But the pathogenesis is still unknown. Pravastatin (PRA), one of HMG‐CoA reductase (HMGCR) inhibitors, has been found to inhibit cells proliferation, including keratinocytes (KCs). In this study, we use PRA to block the mevalonate pathway in KCs with or without the down‐stream intermediate products replenishment. The results demonstrated that PRA strongly inhibited proliferation of KCs and caused the G0 /G1 arrest. When some down‐stream intermediate products were added, only cholesterol (CH) could partially rescue the inhibition effect of PRA on KCs proliferation, but not other products, such as mevalonic acid, farnesyl pyrophosphate or geranylgeranyl pyrophosphate. Mechanistic analysis revealed that PRA down‐regulated expression of cyclin B1, but up‐regulated cyclin E and p21 expression. And PRA increased the phosphorylation level of Protein Kinase B (AKT) but decreased the phosphorylation level of Extracellular Signal Regulated Kinase (ERK1/2). CH could attenuate the elevated cyclin E and activated AKT induced by PRA. These results indicated that CH could rescue the proliferation inhibition of KCs caused by PRA, which laid a foundation for elucidating the pathogenesis of DSAP clearly.